1977
DOI: 10.1021/i260062a602
|View full text |Cite
|
Sign up to set email alerts
|

Vaporization Equilibrium Ratios for CO2 and H2S in Paraffinic, Naphthenic and Aromatic Solvents

Abstract: Vaporization equilibrium ratios (K values) were determined by the chromatographic technique for C02 and H2S at essentially infinite dilution in the methane + n-heptane, methane + methylcyclohexane, and methane + toluene systems at 20, 0, -20, and -40 °F and in the methane + n-octane system at 0 and -20 °C. Measurements covered the pressure range of 100 to 1500 psia. For the methane + n-octane system, the chromatographic data were confirmed by measurements made by classical techniques in a variable-volume windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Calculated Henry's constants for methane and ethane in diphenylmethane and n-hexadecane; comparison with experimental data of Cukor and Prausnitz (1972). experimental measurements of Mundis et al (1977) as shown in Figure 14.…”
Section: Correlation Of Binary Parameters K¡¡mentioning
confidence: 99%
See 1 more Smart Citation
“…Calculated Henry's constants for methane and ethane in diphenylmethane and n-hexadecane; comparison with experimental data of Cukor and Prausnitz (1972). experimental measurements of Mundis et al (1977) as shown in Figure 14.…”
Section: Correlation Of Binary Parameters K¡¡mentioning
confidence: 99%
“…The results shown in Table III are similar to those Figure 14. Calculated K factors for the quaternary system methane-n-octane-carbon dioxide-hydrogen sulfide; comparison with experimental data of Mundis et al (1977).…”
Section: Enthalpymentioning
confidence: 99%
“…Lorsque les phases en équilibre peuvent être considérées idéales, c'est-à-dire lorsque les fugacités des constituants sont proportionnelles à leurs fractions molaires, on peut dire que les coefficients de partage, définis par : Composition des mélanges étudiés par Li et al (1994) Composition of the mixtures investigated by Li et al (1994) Asano et al (1971) (mélange méthane-n-octane) et Mundis et al (1977) (les mélanges C 1 -nC 7 ; C 1 -méthylcyclohexane ; C 1 -toluène et C 1 -nC 8 ) donnent par exemple des graphiques représentant ce coefficient de partage pour le CO 2 et le H 2 S. On constate qu'en réalité, ce coefficient est également fonction de la composition du système. La figure 13, reprise de Eakin et De Vanay (1974), montre cette fonction pour le H 2 S.…”
Section: Coefficients De Partageunclassified
“…Toluene was chosen as the aromatic solvent because of its abundance and low freezing point. Preliminary indications that toluene might be an effective solvent were revealed in an earlier study by Mundis et al (1977).…”
mentioning
confidence: 93%